Evaluasi Efektivitas Gamification Dalam Meningkatkan Pemahaman Siswa Pada Materi Pembelajaran Al-Qur’an di Sdit Bina Insan Banyuresmi - Fitri Nurlatifah Azzahra; Bilal Zakawali Al-Fathoni; Siti Wifa Uswatussholihah; Taupik Hamdani; Rahayu Karyadinata (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to evaluate the effectiveness of gamification in enhancing students' understanding of Qur’anic learning materials at SDIT Bina Insan Banyuresmi. The scope of this study includes the implementation of gamifikasi-based learning approaches within the context of Islamic elementary education. The research employed a quantitative method using a one-group pretest-posttest experimental design. The sample consisted of 25 sixth-grade students. A written test was used as the research instrument. Descriptive analysis showed an increase in the mean score from 77.84 to 84.60. The Wilcoxon Signed Ranks Test indicated a significance value of 0.003 (p < 0.05), confirming a significant difference between pretest and posttest scores. Although the average N-Gain score was affected by outliers, most students experienced moderate improvement. In conclusion, gamification has proven to be significantly effective in improving students' understanding of Qur’anic materials, particularly in fostering active and enjoyable learning environments. Azizah, S. S., Syahidin, & Anwar, S. (2024). IMPLEMENTASI MODEL GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI SISWA PADA PELAJARAN PAI DI SMAN 13 BANDUNG. Jurnal P4I, Vol 4 No 4. Hidayah, N., Abdurrahman, U. K. H., & Pekalongan, W. (n.d.). Efektivitas Penerapan Metode Game-Based Learning Untuk Meningkatkan Minat Belajar Pada Mata Pelajaran Al-Qur’an Hadist Kelas VI DI MIS Sidorejo Tirto Pekalongan. http://e-journal.uingusdur.ac.id/index.php/ijiee Hidayati, N. (2021). Teori Pembelajaran Al Qur’an. Al Furqan: Jurnal Ilmu Al Quran Dan Tafsir, 4(1), 29–40. https://doi.org/10.58518/alfurqon.v4i1.635 Kolb, D. A. (1984). Experiential Learning: Experience As The Source Of Learning And Development. http://www.learningfromexperience.com/images/uploads/process-of-experiential-learning.pdf! Lee, J. J., & Hammer, J. (2011). Gamification in Education: What, How, Why Bother? (Issue 2). https://www.researchgate.net/publication/258697764 Miranda, A., Rahmawati, S., & Adiyono. (2024). GAMIFIKASI DALAM PEMBELAJARAN AL-QUR’AN DAN HADITS DI MADRASAH ALIYAH: MENINGKATKAN MOTIVASI DAN PARTISIPASI SISWA. FIKRUNA: Jurnal Ilmiah Kependiidkan Dan Kemasyarakatan, Vol. 7, No 2(juni-desember). https://doi.org/10.56489/fik.v4i2 Pallant, J. (2020). SPSS; Survival Manual A Step by Step Guide to Data Analysis Using IBM SPSS; 7th Edition. www.routledgetextbooks.com/textbooks/9781760875534 Rosa, E., Destian, R., & Agustian, A. (2024). Inovasi Model dan Strategi Pembelajaran dalam Implementasi Kurikulum Merdeka. In Journal of Education Research (Vol. 5, Issue 3). Safroni, S., Hidayah, U., Tinggi, S., Islam, A., & Probolinggo, M. (n.d.). STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA. Tanjung, W. U., & Namora, D. (2022). Kreativitas Guru dalam Mengelola Kelas untuk Mengatasi Kejenuhan Belajar Siswa di Madrasah Aliyah Negeri. Jurnal Pendidikan Agama Islam Al-Thariqah, 7(1), 199–217. https://doi.org/10.25299/al-thariqah.2022.vol7(1).9796 Vitty binti Fung Ah Chon, Sabariah bte Sharif, & Nuryati binti Md. Saleh. (2024). Gamification for Enhancing Students’ Learning Motivation: A Systematic Review. Journal of Cognitive Sciences and Human Development, 10(2), 19–41. https://doi.org/10.33736/jcshd.7231.2024